EVALUATION OF EARLY CAULIFLOWER (BRASSICA OLERACEA VAR. BOTRYTIS L.) GERMPLASM UNDER TROPICAL CONDITIONS FOR VARIOUS HORTICULTURAL TRAITS - H. M. SANTHOSHA; B. VARALAKSHMI; R. KRISHNA MANOHAR (The Bioscan, 2015)
An experiment was conducted to evaluate the early cauliflower (Brassica oleracea var. botrytis L.) germplasm under tropical conditions. High variability (> 20%) and heritability (> 60%) with high genetic advance (> 20%) was observed for characters like, plant weight, leaf weight, curd size, net curd weight, net plot yield, yield per hectare, protein, vitamin-C and marketable curd weight indicating these characters are governed by additive gene action. Hence, direct selection may be followed for the improvement of early cauliflower for these characters. Marketable curd weight showed highly significant positive association with plant weight, leaf number, leaf length, leaf breadth, leaf weight, curd depth, curd diameter, curd size, net curd weight, net plot yield and yield per hectare at both genotypic and phenotypic levels. So for the genetic improvement of cauliflower through marketable curd weight, selection based on the above characters is desirable. Direct and indirect effects showed that during the selection of superior genotypes in early cauliflower emphasis should be given for plant and leaf parameters like, plant weight, leaf number, leaf length and curd parameters like, curd size and net curd weight.